Brief early antibiotic exposure (≤2 days) is not associated with disruption of gut microbiome in very low birth weight infants - Aoki, Yoshinori; Tate, Mayumi; Ochiai, Kayo; Tsuchimochi, Kohei; Mizuguchi, Uiko; Okazaki, Kaoru; Moritake, Hiroshi (Frontiers in Microbiology, 2026)
Early empirical antibiotic therapy is common in preterm and very low birth weight (VLBW) infants but may disrupt the developing gut microbiome. However, the effects of brief antibiotic courses remain unclear, particularly in the most immature infants. In this prospective multicenter cohort study, we examined gut microbiome trajectories in VLBW infants (many of whom were extremely preterm) receiving no antibiotics, a short course (≤2 days), or prolonged exposure (≥3 days). Serial stool samples were analyzed using 16S rRNA gene sequencing. Microbiome composition and diversity in the short-course group were similar to those in unexposed infants at all timepoints, indicating that brief antibiotic exposure did not disrupt microbial development. In contrast, prolonged exposure was associated with transient dysbiosis characterized by reduced Bifidobacterium abundance and lower alpha diversity, with partial recovery by discharge. These findings suggest that limiting empirical antibiotic therapy to ≤2 days (48 h) when infection is unconfirmed may not disrupt microbiome development even in highly immature preterm VLBW infants, supporting evidence-based antibiotic stewardship in neonatal intensive care.